Hepatorenal Syndrome: direct treatment costs and characteristics of patients admitted to intensive care - Franciele Robes Hortelã; Rodrigo Sfredo Kruger; Valéria Filomena de Oliveira; Hipolito Carraro Junior; Dominique Araújo Muzzillo; Sérgio Candido Kowalski (Einstein (São Paulo))
ABSTRACT Objective The purpose of this study was to describe the direct medical costs incurred in Brazil for the treatment of Hepatorenal Syndrome in intensive care and intermediate therapy care units, and to investigate the impact of this syndrome on patient survival. Methods This longitudinal observational retrospective study included patients with Hepatorenal Syndrome admitted to the intensive and intermediate therapy care units of a public tertiary hospital. The cost generated by each patient was the sum of the direct costs and overheads. Results Forty-four patients with 49 episodes of suspected Hepatorenal Syndrome were analyzed, 73% male, with a mean age of 55 years (SD= 11). Diagnosis was presumed in 21 episodes (43%), because not all of the Ascites International Club’s criteria were met. Alcoholic cirrhosis was the main etiology (43%); 59% of the patients were Child-Pugh Class C at admission, with a mean (SD) model for end-stage liver disease score of 24.6 (8). Seventy-seven percent of the patients died, 32% from multiple organ failure, 29% of septic shock and 27% of hypovolemic shock. The median (IQR) of the total treatment cost for each patient was Int$14,819 (8,732-23,854). The median (IQR) length of intensive care unit stay in intensive care was 11 days (7-19). Patients with a presumed diagnosis did not have a higher hospitalization cost (p=0.249) than those with true Hepatorenal Syndrome. Conclusion The treatment of Hepatorenal Syndrome represents a significant cost, and new resource allocation in strategic areas, such as the treatment and monitoring of patients with cirrhosis, is necessary to improve their outcomes.